Tinjauan Hukum Islam dalam Menyikapi Aksi Demonstrasi - Aliefia Qatrunnada; Muannif Ridwan (Jurnal Indragiri Penelitian Multidisiplin, 2022)
Democracy is a system of government whose sovereignty is in the hands of the people, the highest power is in the decisions of the people, government of the people, by the people and for the people. It is clear that the role of the people in democracy is very important. Demonstrations are manifested by the freedom of the public to voice their opinions and express themselves in public, which is a reflection of the fulfillment of the people's right to get space for submitting protests against a policy. In the perspective of Islamic law, democracy is an ijtihad carried out in order to achieve the maslahah of implementing solid and responsible development management by adhering to the principles of democracy.